(untitled) (Damascus University Journal for legal sciences, 2024)
International crime is one of the main problems of concern to the international community; Given the fact that this crime, as an international phenomenon, poses a real threat to the interests, security and stability of states; And because of the serious effects it has on states and individuals alike; More importantly, it directly affects the security and stability of the international community as a whole, at a time when there is an urgent need to develop effective solutions that ensures the reduction of abuses and violations committed by countries towards other countries, which bear the features of international crimes. This study attempted to shed light on international crime, research its elements and characteristics, and the limits of the responsibility of states and individuals for it, and distinguish it from similar concepts, in addition to researching its reality and its most prominent models, in the light of the provisions contained in the Rome Statute of the International Criminal Court of 1998, as The main regulating reference for the provisions of international crime